Systemic antisense therapeutics inhibiting DUX4 expression ameliorates FSHD-like pathology in an FSHD mouse model. Issue 15 (13th May 2021) - Lu-Nguyen, Ngoc; Malerba, Alberto; Herath, Shan; Dickson, George; Popplewell, Linda
Abstract: Aberrant expression of the double homeobox 4 ( DUX4 ) gene in skeletal muscle causes muscle deterioration and weakness in Facioscapulohumeral muscular dystrophy (FSHD). Since the presence of a permissive pLAM1 polyadenylation signal is essential for stabilization of DUX4 mRNA and translation of DUX4 protein, disrupting the function of this structure can prevent expression of DUX4. We and others have shown promising results using antisense approaches to reduce DUX4 expression in vitro and in vivo following local intramuscular administration. Here we demonstrate that further development of the antisense chemistries enhances in vitro antisense efficacy. The optimal chemistry was conjugated to a cell-penetrating moiety and was systemically administered into the tamoxifen-inducible Cre-driver FLExDUX4 double-transgenic mouse model of FSHD. After four weekly treatments, mRNA quantities of DUX4 and target genes were reduced by 50% that led to 12% amelioration in muscle atrophy, 52% improvement in in situ muscle strength, 17% reduction in muscle fibrosis and prevention of shift in the myofiber type profile. Systemic DUX4 inhibition also significantly improved the locomotor activity and reduced the fatigue level by 22%. Our data demonstrate that the optimized antisense approach has potential of being further developed as a therapeutic strategy for FSHD.